2012
DOI: 10.1007/s10147-012-0454-0
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic impact of pretreatment C-reactive protein for patients with metastatic renal cell carcinoma treated with tyrosine kinase inhibitors

Abstract: CRP has a significant impact on overall survival of patients with metastatic renal cell carcinoma carcinoma treated with tyrosine kinase inhibitors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
31
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 24 publications
2
31
0
Order By: Relevance
“…Jabs WJ et al showed that activity of the IL-6/CRP network in RCC patients contributes to the acute-phase reaction in local inflammatory processes [29]. Other clinical data also showed that elevated CRP level is associated with poorer OS of RCC patients [30, 31] and CRP has a significant impact on OS of metastatic RCC patients treated with a tyrosine kinase inhibitor, either sunitinib or sorafenib [32, 33]. …”
Section: Discussionmentioning
confidence: 99%
“…Jabs WJ et al showed that activity of the IL-6/CRP network in RCC patients contributes to the acute-phase reaction in local inflammatory processes [29]. Other clinical data also showed that elevated CRP level is associated with poorer OS of RCC patients [30, 31] and CRP has a significant impact on OS of metastatic RCC patients treated with a tyrosine kinase inhibitor, either sunitinib or sorafenib [32, 33]. …”
Section: Discussionmentioning
confidence: 99%
“…CRP has been shown to be a non-specific biomarker in patients with various stages of RCC who receive surgery (13-16,18-21), immunotherapy (13,15,17,22,23) and molecular-targeted therapy (9)(10)(11)(12). CRP has a promising role in predicting survival among patients with localized and metastatic RCC.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have revealed a prognostic role for CRP in the outcome of sunitinib treatment (9)(10)(11)(12). Normal pretreatment CRP levels predict a higher response rate and better survival among patients undergoing sunitinib treatment (9,11).…”
Section: Introductionmentioning
confidence: 99%
“…A total of 43 eligible studies (7, 490 patients) were identified for this meta-analysis (25 for RCC (Atzpodien et al, 2003;Bromwich et al, 2004;Casamassima et al, 2005;Peccatori et al, 2005;Ito et al, 2006;Lamb et al, 2006;Vogl et al, 2006;Karakiewicz et al, 2007;Komai et al, 2007;Ramsey et al, 2007;Kawata et al, 2008;Ramsey et al, 2008;Tanaka et al, 2008;Iimura et al, 2009;Jagdev et al, 2010;Cho et al, 2011;Falkensammer et al, 2011;Bedke et al, 2012;Fujita et al, 2012;Sim et al, 2012;Steffens et al, 2012;de Martino et al, 2013;Yasuda et al, 2013), 10 for UC (Hilmy et al, 2005;Hilmy et al, 2006;Saito et al, 2007;Yoshida et al, 2008;Gakis et al, 2011;Saito and Kihara, 2011;Ishioka et al, 2012;Obata et al, 2012;Tanaka et al, 2012;Stein et al, 2013), and 8 for PC (McArdle et al, 2006;Beer et al, 2008;Nakashima et al, 2008;McArdle et al, 2010;Pond et al, 2012;Prins et al, ...…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%